COMPARISON OF ANTHROPOMETRIC PARAMETERS BETWEEN OBESE MALE PARTICIPANTS WITH AND WITHOUT OBSTRUCTIVE SLEEP APNEA - Shagufta Khaliq; Mudassar Ali Roomi; Muniza Saeed; Komal Iqbal; Shaheena Naz; Huma Hussain (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: The most common risk factors for Obstructive Sleep Apnea includes: Obesity and increased neck circumference in male gender. The objective of the study was to compare the anthropometric parameters between obese male participants with and without obstructive sleep apnea (OSA). METHODOLOGY: Study was conducted at Department of Physiology, Post Graduate Medical Institute, Lahore during 24 August 2014 to 26 May 2015. Obese males (n=64) with body mass index (BMI) >25kg/m2 and aged 20-45 years were recruited by convenience sampling. Screening of OSA was made by two subjective tools: STOP BANG Questionnaire, and Berlin Questionnaire while final diagnosis was made by overnight portable pulse oximetry. Study population was divided into two groups. Group-I comprised of 32 obese males with OSA. Group II had 32 obese males without OSA. BMI, neck circumference, and waist circumference were measured by standard methods.Comparison of variables was done between the groups by Mann-WhitneyUtest and t-test. RESULTS: BMI was higher in group-I than in group-II (p=0.004). Median BMI for group-I was 30.83 (28.16–32.80) and for group-II was 27.99 (26.59–30.08) Kg/m2. A significantly higher neck circumference (p<0.001) was present in group-I (41.95±2.40cm) than group-II (39.66±2.07cm). Moreover, significantly higher median waist circumference (p<0.001) was present in group I (107.5cm) as compared to group-II (98.5cm). CONCLUSION: Anthropometric parameters (BMI, neck circumference, and waist circumference) are higher in obese individuals with OSA as compared to obese males without OSA.